2015
DOI: 10.1161/circulationaha.115.014538
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letters Regarding Article, “Can Intensive Exercise Harm the Heart? You Can Get Too Much of a Good Thing”

Abstract: We thank our colleagues for their interest in our article pertaining to the controversial topic of whether intense exercise can cause cardiac injury.1 Drs Scott and Haykowsky argue that we did not adequately address exercise dose as defined by both duration and intensity. We believe that this critique may be reasonably leveled at the entire field of exercise cardiology in which there is no standard definition of what constitutes an athlete, intense exercise, or endurance exercise. For example, we have previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 6 publications
4
50
0
1
Order By: Relevance
“…The benefits of moderate exercise are indisputable, and physical activity should be encouraged in all individuals including those with chronic cardiac disease. However, although the analysis of the cardiovascular consequences of different intensity of endurance exercise was beyond the scope of the present study, the discrepancies found among the arrhythmic effects of different endurance disciplines may support the theory that more extreme endurance exercise may be associated with an excess of arrhythmias contrary to the plethora of beneficial effects offered by moderate endurance training …”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The benefits of moderate exercise are indisputable, and physical activity should be encouraged in all individuals including those with chronic cardiac disease. However, although the analysis of the cardiovascular consequences of different intensity of endurance exercise was beyond the scope of the present study, the discrepancies found among the arrhythmic effects of different endurance disciplines may support the theory that more extreme endurance exercise may be associated with an excess of arrhythmias contrary to the plethora of beneficial effects offered by moderate endurance training …”
Section: Discussionsupporting
confidence: 54%
“…However, although the analysis of the cardiovascular consequences of different intensity of endurance exercise was beyond the scope of the present study, the discrepancies found among the arrhythmic effects of different endurance disciplines may support the theory that more extreme endurance exercise may be associated with an excess of arrhythmias contrary to the plethora of beneficial effects offered by moderate endurance training. 34,35 Finally, in our study we also observed greater T-wave amplitude at the finish-line evaluation as compared with ECG data collected the day before the competition, in absence of relevant differences between men and women. 36 During exercise T-wave magnitude tends to lessen, showing a marked increase in the first minutes of recovery.…”
supporting
confidence: 60%
“…Left ventricular (LV) size and function have been described in detail using two-dimensional (2D), M-mode, pulsed wave (PW) Doppler and more recently tissue Doppler imaging (TDI) and twodimensional speckle tracking (2DST) measurements [1][2][3][4][5][6]. Recent evidence also suggests that, in man, training has a pronounced impact on RV structure and function due to the disproportionate rise in pulmonary artery pressure during exercise [8]. Recent evidence also suggests that, in man, training has a pronounced impact on RV structure and function due to the disproportionate rise in pulmonary artery pressure during exercise [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, significant RV enlargement and reduced RV reformation has been documented in much larger cohorts of young elite athletes 2. Not all athletes are equal,3 and these seemingly incongruent results might be explained by the fact that the athletes in the Teske's study were performing 4–5 times the amount of weekly training. There are many more studies than these, and we agree that there is evidence to both support and refute the idea of permanent cardiac remodelling of the RV, left ventricle (LV) and the atria.…”
mentioning
confidence: 99%
“…Our analysis suggests that this may be missing the point. A syndrome of proarrhythmic remodelling of the RV which seems to be associated with long-term endurance exercise training has been described in humans3 4 and in rats 5. We believe that it would be incorrect as clinicians and scientists to not at least entertain the possibility that high-intensity endurance exercise may be associated with these potentially life-threatening conditions.…”
mentioning
confidence: 99%